2014
DOI: 10.1038/gene.2014.65
|View full text |Cite
|
Sign up to set email alerts
|

Human natural killer cell microRNA: differential expression of MIR181A1B1 and MIR181A2B2 genes encoding identical mature microRNAs

Abstract: Natural killer (NK) and T lymphocytes share many properties, yet only NK cells respond rapidly to infection and cancer without pre-activation. We found that few microRNAs (miRNAs) differed significantly between human NK and T cells. Among those miRNAs, miR-181a, and miR-181b levels rose during NK cell differentiation. Prior studies indicate that miR-181a and miR-181b are critical for human NK cell development and are co-transcribed from genes on chromosome 1 (MIR181A1B1) and on chromosome 9 (MIR181A2B2). We ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…The miR-181 family plays diverse roles in regulating key aspects of cellular growth, development, inflammatory response, differentiation, and autophagy. 24 , 25 , 53 , 54 , 55 , 56 Bioinformatic analysis and our results indicated that miR-181a-5p targets P parα . We found that the intracellular DNA damage and apoptosis induced by overdose WY-14643 treatment were significantly reduced by the ectopic expression of miR-181a-5p.…”
Section: Discussionsupporting
confidence: 53%
“…The miR-181 family plays diverse roles in regulating key aspects of cellular growth, development, inflammatory response, differentiation, and autophagy. 24 , 25 , 53 , 54 , 55 , 56 Bioinformatic analysis and our results indicated that miR-181a-5p targets P parα . We found that the intracellular DNA damage and apoptosis induced by overdose WY-14643 treatment were significantly reduced by the ectopic expression of miR-181a-5p.…”
Section: Discussionsupporting
confidence: 53%
“…3). Recent data show that specific inflammatory cytokines and innate signals, including IL-12/IL-18 or IL-15, and TLR signaling, promote microRNA (miRNA) miR-181a and miR-148a expression in human and murine leukocytes (41, 42) and miR-148a has been shown to directly limit Bach2 expression (43). Altered regulation of Bach2 may function as a mechanistic link by which specific inflammatory cytokines and miRNA regulate T cell differentiation, survival and memory formation.…”
Section: Bach2 Regulation Of Memory T Cell Development and Functionmentioning
confidence: 99%
“…miRNA expression is closely associated with cellular processes such as cell growth, proliferation, and apoptosis. Many studies have investigated the roles of miRNAs in cancer, inflammation, and immunity [ 3 4 5 ]. Recent studies demonstrated that miRNA profiles can be determined from blood [ 6 7 8 ], including circulating miRNAs and those associated with cancer or damaged tissues [ 9 10 ].…”
Section: Introductionmentioning
confidence: 99%